Interactive Sociocultural Teaching Materials Based on CRT With Lectora As Innovation in Citizenship Education - Fauzatul, Fauzatul Ma'rufah Rohmanurmeta; Putri, Widyarini Susilo Putri (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to produce interactive sociocultural teaching materials based on CRT with lectora to improve student learning outcomes that contain information about Indonesian cultural diversity. Method: This study is the development of interactive sociocultural teaching materials based on CRT with lectora using the 4D model from Thiagarajan, which includes Defining, Designing, Developing, and Disseminating. Meanwhile, the study subjects were grade IV students of Public Elementary School 1 Plalangan Ponorogo to determine the effectiveness of interactive teaching materials. Results: The interactive sociocultural teaching materials based on CRT with Lectora were considered valid by experts, with an average score reaching the very valid category. This teaching material is efficient, as evidenced by the ease of use by teachers and the high level of student readability (83% -92%). The teaching materials effectively improve student learning outcomes, with an average N-Gain Score of 0.67 (moderate to high category). Interactive teaching materials support sociocultural learning based on the CRT approach, making students learn according to their abilities. Novelty: Sociocultural interactive teaching materials use CRT as an approach to learning, which has not been widely applied in developing Citizenship Education teaching materials, especially for the material on the diversity of Indonesian culture. This teaching material was developed using Lectora, which can produce interesting and innovative Citizenship Education teaching materials.